Invasive mealybug Pseudococcus jackbeardsleyi Gimpel and Miller on Curcuma aeruginosa Roxb. on the seed rhizome in storage: a record of a new host - Rohimatun; Nida Nur Rahmah; Dewi Sartiami; Mahindra Dewi Nur Aisyah; Miftakhurohmah Miftakhurohmah; Melati; Devi Rusmin; Tri Lestari Madiningsih (Journal of Plant Protection Research)
Mealybug is a renowned pest known to attack agricultural products from the field to the post-harvest process, such as on the seed rhizomes of Curcuma aeruginosa. Therefore, this study aimed to examine and identify the species of mealybug on the seed rhizomes of C. aeruginosa based on morphological and molecular characteristics. Fifty mealybugs were collected from the seed rhizomes of C. aeruginosa in the storage room in Bogor (Indonesia) using a soft brush. They were transferred to new C. aeruginosa rhizomes without any other insects present. Morphological identification based on observation of mounted specimens of 10 female adults and six for molecular identification. The primer pair that amplified the mitochondrial cytochrome oxidase I (COI) gene was used to study the molecular characteristics and was continued with direct sequencing and sequence analysis. The results showed that the morphological characteristics of the mounted specimen were close to those of Pseudococcus jackbeardsleyi. Amplification of the COI gene yielded DNA bands measuring 490 base pairs (bp), while homology and phylogeny analysis confirmed the morphological identification. Based on BLAST analysis, the similarity of COI genes of mealybugs in this study was above 99% with other P. jackbeardsleyi. The study specimen was identified as P. jackbeardsleyi on the seed rhizomes of C. aeruginosa by comparing the morphological features of insect specimens and results of the species available in GeneBank. This result represented the first documented report about the presence of the species in storage.